Manajemen risiko bank syariah di era digital: strategi, inovasi, dan tantangannya - Salsabil, Rihhadatul Aisy (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the strategies, innovations, and challenges faced by Islamic banks in implementing risk management in the digital era. The method used is a literature study, by collecting secondary data from various scientific sources related to Islamic banking, risk management, and the development of financial technology. The results of the study indicate that digitalization has a significant impact on the complexity of risks faced by Islamic banks, such as cyber risk, data leakage, and compliance with Islamic principles in digital systems. Therefore, an adaptive risk management strategy is needed, such as improving technological infrastructure, strengthening information security systems, HR training, and cooperation with external institutions. This study provides an important contribution in formulating effective steps to maintain the stability and competitiveness of Islamic banks in facing the dynamics of the digital era.